2017
DOI: 10.1016/j.jbmt.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic manipulative treatment for low back and pelvic girdle pain during and after pregnancy: A systematic review and meta-analysis

Abstract: This review suggests OMT produces clinically relevant benefits for pregnant or postpartum women with LBP. Further research may change estimates of effect, and larger, high-quality randomized controlled trials with robust comparison groups are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 37 publications
0
33
0
3
Order By: Relevance
“…Another meta-analysis found that even during and after pregnancy, osteopathic manipulative treatment for low back and pelvic girdle pain during and after pregnancy gave clinically relevant benefits [ 37 ]. A meta-analysis of randomized controlled trials (RCTs) published in 2018 showed that exercise decreased the risk of low back pain in pregnancy by 9% [pooled risk ratio (RR) = 0.91; 95% CI 0.83–0.99; I 2 = 0%, seven trials; n = 1175] [ 38 ].…”
Section: Pregnancymentioning
confidence: 99%
“…Another meta-analysis found that even during and after pregnancy, osteopathic manipulative treatment for low back and pelvic girdle pain during and after pregnancy gave clinically relevant benefits [ 37 ]. A meta-analysis of randomized controlled trials (RCTs) published in 2018 showed that exercise decreased the risk of low back pain in pregnancy by 9% [pooled risk ratio (RR) = 0.91; 95% CI 0.83–0.99; I 2 = 0%, seven trials; n = 1175] [ 38 ].…”
Section: Pregnancymentioning
confidence: 99%
“…Osteopathy is a complementary touch-based manual medicine primarily used by different age groups of patients ( Licciardone et al, 2013 ; Cerritelli et al, 2014 , 2015b ; Pizzolorusso et al, 2014 ; Luciani et al, 2015 , 2018 ; Schwerla et al, 2015 ; Steel et al, 2017 ) and in a wide variety of clinical conditions ( Cerritelli et al, 2011 , 2015a , 2016a , 2017b ; Cicchitti et al, 2015 ; Ruffini et al, 2016 ; Franke et al, 2017 ; Lanaro et al, 2017 ). Several studies showed positive clinical effects as compared to sham, placebo, usual care or physical devices ( Pizzolorusso et al, 2011 ; Cerritelli et al, 2013 , 2015a , 2016b ; Martelli et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores investigaram em seus estudos o efeito de hipoalgesia pela manipulação visceral sobre os tecidos osteomioarticulares, sendo constatado uma melhoria de tais parâmetros sobre o nível metamérico correspondente a estrutura em que foi encontrada maior tensão fáscial ou disfunção. Tais conclusões fundamentaram parâmetros para a realização de novos estudos como este apresentado [24][25][26][27][28][29][30].…”
Section: Discussionunclassified